2014
DOI: 10.1530/jme-14-0184
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the DRY motif and intracellular loop 2 of human melanocortin 3 receptor

Abstract: The melanocortin 3 receptor (MC3R) regulates several physiological functions, including feed efficiency, nutrient partitioning, fasting response, natriuresis, and immune reactions. Naturally occurring mutations in the MC3R gene have been shown to be associated with increased adiposity and lung diseases such as tuberculosis and cystic fibrosis. The DRY motif at the cytoplasmic end of transmembrane domain 3 (TM3) and the second intracellular loop 2 (ICL2) are known to be important for receptor function in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
(66 reference statements)
4
23
0
Order By: Relevance
“…Receptor retention or mislocalization, which has previously been described as the major defect for human disease caused by GPCR mutations ( Tao 2006 ; Tao and Conn 2014 ), was not observed in present study. Similarly, in our studies on the second and third intracellular loops, we also showed that the alanine mutants are expressed normally at the cell surface ( Huang and Tao 2014 ; Wang and Tao 2013 ).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Receptor retention or mislocalization, which has previously been described as the major defect for human disease caused by GPCR mutations ( Tao 2006 ; Tao and Conn 2014 ), was not observed in present study. Similarly, in our studies on the second and third intracellular loops, we also showed that the alanine mutants are expressed normally at the cell surface ( Huang and Tao 2014 ; Wang and Tao 2013 ).…”
Section: Discussionsupporting
confidence: 81%
“…Unbalanced cAMP and ERK1/2 signaling was reported in some human MC4R mutants ( He and Tao 2014 ; Huang and Tao 2012 ; Mo et al 2012 ) (reviewed in ( Tao 2014 )). In our recent study of the DRY motif and intracellular loop 2 of hMC3R, the presence of this biased signaling was also suggested ( Huang and Tao 2014 ). To test it further, in the current study, the ERK1/2 phosphorylation levels of nine hMC3R mutants, including eight binding- or signaling-defective mutants (P333A, I335A, Y336A, E342A, L343A, R344A, I350A, and L351A) which led to less than 20% cAMP production compared with WT hMC3R, and one constitutively active mutant (F347A) with enhanced basal cAMP activity, were investigated using western blots.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations